The role of organoids in cancer research - Zhen Fang; Peijuan Li; Fengying Du; Liang Shang; Leping Li (Experimental Hematology & Oncology, 2023)
Abstract Organoids are established through in vitro 3D culture, and they can mimic the structure and physiological functions of organs or tissues in vivo. Organoids have attracted much attention in recent years. They can provide a reliable technology platform for cancer research and treatment and are a valuable preclinical model for academic research and personalized medicine. A number of studies have confirmed that organoids have great application prospects in new drug development, drug screening, tumour mechanism research, and precision medicine. In this review, we mainly focus on recent advances in the application of organoids in cancer research. We also discussed the opportunities and challenges facing organoids, hoping to indicate directions for the development of organoids in the future.